THE 3 - IN - 1 SKYLIGHT SHADING DEVICE FOR SURABAYA INDONESIA: AN ENERGY SAVING AND CONSIDERATIONS - Danny Santoso Mintorogo (Dimensi: Journal of Architecture and Built Environment, 2004)
In terms of energy saving strategies and proper use of skylight modules in architectural buildings in the tropical climate, this paper will give evidence of how appropriate use of skylight modules installed on buildings in the tropical zone compared to the ones in the subtropical climate. In the tropical humid climate, Indonesia has received huge amount of global direct and diffuse radiations on horizontal roofs throughout the year, approximately 575 watts per square meter of radiation will impact on flat roofs or skylights on a sunny day in Surabaya city. Moreover, the hot season is longer, from mid May to mid December, than the wet season. Most of the commercial and institution buildings are equipped with Western skylight styles in Surabaya without any modifications. The three-in-one skylight device is the system that will control daylight, shade direct solar heat radiation, and collect solar hot water at the same time. The concept of the three-in-one shading device has three goals: first of all, it is to shade horizontal or tiled skylight on roof providing shading devices. Secondly, the series of circular cube as shading device will bounce and scatter the direct sunlight into the space below enhancing daylight patterns. Finally, while shading and bouncing direct sunlight, those series of circular shading water pipes would also collect the solar heat radiation getting hot water. Each system works nicely to block, to scatter, and to obtain the solar heat radiation for energy saving in green architecture and clean environmental living zones.